Histoire du Syndicalisme Agricole qu Québec. UCC-UPA 1924-1984 - Robert, Jean-Claude (Labour / Le Travail, 1988)
This article reviews the book, "Histoire du Syndicalisme Agricole au Québec. UCC-UPA, 1924-1984," by Jean-Pierre Kesteman, Guy Boisclair & Jean-Marc Kirouac.